Low-cost hydrophobic phenolic aldehyde-based aerogel fiber composite material as well as preparation method and application thereof

By replacing phenolic resin with glass fiber and using vacuum ion microwave treatment, a low-cost, high-strength, and hydrophobic phenolic-based aerogel fiber composite material was prepared. This solved the problems of high cost and easy moisture absorption of phenolic-silica aerogel fiber composite materials, and enhanced its application potential in construction and new energy vehicles.

CN119287667APending Publication Date: 2025-01-10NANJING TECH UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411458571.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing phenolic-silicone aerogel fiber composite materials are costly and prone to moisture absorption, making it difficult to meet the high-performance requirements of building insulation materials.

Method used

Low-cost hydrophobic phenolic aerogel fiber composites were prepared by partially replacing phenolic resin with glass fiber, and combining silicate ester, silane coupling agent and modified reinforcing material through vacuum ion microwave treatment.

Benefits of technology

It reduces material costs, improves mechanical and hydrophobic properties, enhances thermal insulation performance, simplifies the manufacturing process, and is suitable for thermal insulation materials used in buildings and new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287667A_ABST
    Figure CN119287667A_ABST
Patent Text Reader

Abstract

The invention discloses a low-cost hydrophobic phenolic aldehyde-based aerogel fiber composite material and a preparation method and application thereof.The method comprises the steps that phenolic aldehyde serves as a raw material, ethyl alcohol serves as a solvent, an alkaline silicon source serves as a self-catalyst, and aluminum oxide, talcum powder, carbon nano tubes and glass hollow microspheres serve as dopants; the silicon-hybridized phenolic aldehyde-based aerogel composite material is prepared by compounding the silicon-hybridized phenolic aldehyde-based aerogel with the fiber felt, hydrophobic groups are accessed through vacuum high-energy-state ion microwaves, the materials and the process are simple, the microstructure controllability is good, and the prepared aerogel material has the characteristics of high strength, high flame retardance, high temperature resistance, aging resistance, good hydrophobicity and the like; the problem that traditional phenolic aerogel is poor in mechanical property and the problems that traditional building materials are prone to burning and being affected with damp are effectively solved, and application and development of aerogel materials in the fields of buildings, aviation and the like are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aerogel materials, and in particular relates to a low-cost hydrophobic phenolic-based aerogel fiber composite material and a preparation method and application thereof. Background Art

[0002] With the continuous improvement of my country's building energy-saving standards, higher requirements are also placed on thermal insulation materials. Traditional insulation materials have difficulty meeting the increasingly high building energy-saving standards in terms of thermal insulation performance. Increasing thickness will lead to reduced safety and increased costs. It is urgent to develop "low-cost, low thermal conductivity, high temperature resistance, and combustion resistance" high-performance building insulation materials.

[0003] Silica aerogel is currently the thermal insulation material with the lowest thermal conductivity, but it has an international problem of poor mechanical properties. Phenolic RF aerogel is synthesized with resorcinol and formaldehyde as monomers, but the preparation process of phenolic aerogel is complicated and the cycle is long, and the simple polymer aerogel has poor heat resistance and fire retardant properties. At present, by hybridizing phenolic resin with silicon-based materials, the three-dimensional network structure of phenolic resin can be closely cross-linked with the silicon-oxygen network, and aerogel materials with both thermal insulation and flame retardant properties can be successfully prepared [Xu Wenjie, et al. "Preparation and Performance Study of Organic Silicon / Phenolic Hybrid Aerogel." Journal of Chemical Industry 74.08(2023):3572-3583.]. However, such materials still face problems such as complex preparation process and susceptibility to moisture, and the mechanical properties after composite have not yet met the practical application requirements of building insulation materials. Fiber composite technology is an effective method to improve material performance. By combining aerogel with fiber materials, lightweight composite materials with strong mechanical properties and easy processing can be prepared [Fu Yu, et al. "Research Progress on Thermal and Mechanical Properties of Aerogel / Fiber Composites." Materials Engineering 51.11(2023):1-13.]. However, phenolic-silica aerogel fiber composites still have the problems of high cost and easy moisture absorption, which limits their wide application in building insulation materials. Summary of the invention

[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing a low-cost, high-strength heat-insulating, flame-retardant and hydrophobic integrated phenolic-based aerogel fiber composite material in view of the deficiencies in the prior art.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a low-cost hydrophobic phenolic-based aerogel fiber composite material comprises the following steps: (1) Solution A preparation: Phenol, aldehyde, phenolic resin, alcohol, silicate, and silane coupling agent are mixed evenly at a molar ratio of x:2x:1-x:2.5:0.3:0.45 to obtain solution A; wherein x<1; (2) Preparation of reinforced fiber felt: chopped glass fiber, chopped ceramic fiber, binder and water are mixed in a mass ratio of y:1 to y:3:25 to obtain a mixed slurry, wherein y is less than 1; then 3 to 5% by mass of the modified reinforcing material is added to the mixed slurry, the mixture is fully stirred and mixed, and then wet filtered to obtain a reinforced composite fiber felt; (3) impregnating the reinforced composite fiber felt obtained in step (2) into solution A in step (1), reacting at 20-50° C. for 3-5 hours to obtain a wet gel fiber composite material; (4) drying, aging, solvent replacement, and drying the wet gel fiber composite material obtained in step (3) to obtain a silicon-modified phenolic-based aerogel fiber composite material; (5) Solution B preparation: ethanol and silane hydrophobic agent are mixed at a molar ratio of 1:0.05-0.2 to obtain solution B; (6) The silicon-modified phenolic-based aerogel fiber composite material obtained in step (4) is subjected to vacuum ion microwave treatment using solution B to obtain.

[0006] Preferably, in step (1), the silicate is methyl orthosilicate or ethyl orthosilicate; the phenol is any one of catechol, resorcinol or hydroquinone; the aldehyde is any one of formaldehyde, acetaldehyde and butyraldehyde; and the silane coupling agent is any one of 3-aminopropyltriethoxysilane and 3-epoxypropyltriethoxysilane.

[0007] Preferably, in step (2), the chopped ceramic fibers have a length of 5-10 mm and a density of 0.16-0.18 g / cm 3 The chopped glass fibers have a length of 5 to 10 mm and a density of 0.09 to 0.12 g / cm 3 ; The binder is one of ethyl silicate and sodium silicate; the planes of the obtained reinforced composite fiber felt are partitioned.

[0008] Preferably, in step (2), the modified reinforcing material is a mixture of alumina, carbon nanotubes, talcum powder, and hollow glass microspheres in a molar ratio of 0.5-1:0.5-1:0.5-1:1-3; the particle size of the alumina is 250-500 nm, and the bulk density is 3.9-4.2 g / cm 3 The diameter of the carbon nanotubes is 30-80 nm, and the length is 10-30 µm; the mesh size of the talcum powder is 2000-3000, and the bulk density is 2.7-2.8 g / cm 3 The hollow glass microspheres have a particle size of 40-60 µm and a bulk density of 0.49-0.68 g / cm 3 .

[0009] Preferably, in step (2), firstly, a binder is added to water and stirred until dissolved, fibers are added in portions and stirred for 20 to 30 minutes, and then 3 to 5% of a modified reinforcing material is added in a total weight ratio; the modified reinforcing material needs to be washed with ethanol, immersed in an ethanol-water solution of a silane coupling agent for 5 to 7 hours, then filtered, and dried in an oven for 3 to 5 hours.

[0010] Preferably, in step (2), the wet filtration is carried out by any one of low-pressure suction filtration, plate pressure filtration and mesh filtration.

[0011] Preferably, in step (3), the reinforced composite fiber felt and the solution A are mixed in a volume ratio of 1:1-1.5.

[0012] Preferably, in step (4), the drying temperature is 50-80°C; the wet gel aging conditions are: aging at 50-80°C for 8-12 days, and the aging liquid is one of ethanol, acetone or n-hexane; the drying method is one of CO2 supercritical drying, microwave plasma drying or atmospheric pressure drying.

[0013] Preferably, in step (5), the silane hydrophobic agent is hexamethyldisilazane and / or dimethyldiethoxysilane.

[0014] Preferably, in step (6), the vacuum ion microwave treatment method is: in a closed container, solution B is placed at the bottom, the silicon-modified phenolic-based aerogel fiber composite material is suspended in the middle, evacuated to less than 100 Pa, and heated to 35-50°C, treated with 2-3 GHz microwave radiation for 30s-1min, then allowed to react for 4-10min, and then subjected to microwave radiation treatment, and repeated 2-3 times.

[0015] Furthermore, the present invention also claims protection for the low-cost hydrophobic phenolic-based aerogel fiber composite material prepared by the above preparation method.

[0016] Furthermore, the present invention also claims to protect the use of the above-mentioned low-cost hydrophobic phenolic-based aerogel fiber composite material as a thermal insulation material in buildings and new energy vehicles. Beneficial Effects

[0017] (1) The present invention provides a method for preparing a low-cost, high-strength, heat-insulating, flame-retardant and hydrophobic integrated phenolic-based aerogel fiber composite material. Phenolic resin and glass fiber are used as raw materials, ethanol is used as solvent, and alkaline silicon source is used as self-catalyst. Phenolic resin and glass fiber partially replace part of phenol, aldehyde raw materials and ceramic fibers respectively, which reduces costs and enhances the pore structure to a certain extent (the cost of raw materials is reduced by 20-30% without affecting the pore structure of aerogel); vacuum ion microwave treatment materials are used, and vacuum high-energy ion microwaves are connected to hydrophobic groups, which can effectively improve the hydrophobic properties of aerogels. The process is simple, efficient, and can extend the service life of the material. The doping of alumina, carbon nanotubes, talcum powder and hollow glass microspheres enhances the aerogel in multiple dimensions, improves the structural strength and effectively improves the thermal insulation performance of aerogels, thereby promoting the application and development of aerogel materials in the fields of construction, military industry, and aerospace.

[0018] (2) The preparation process of the present invention is simple, the cycle is short, and it is convenient for industrial production. The prepared phenolic-based aerogel composite material is partially replaced by phenolic resin and glass fiber, which greatly reduces the material cost, has good hydrophobic, heat-insulating and flame-retardant properties, and efficiently and long-term blocks heat conduction, thereby effectively improving the problems of building insulation and fire prevention. The prepared phenolic-based aerogel composite material is a large-area whole block, which improves the mechanical properties and promotes the application and development of aerogel materials in the fields of construction, automobiles, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0020] Figure 1 This is a sample picture prepared in Example 3.

[0021] Figure 2 The SEM images show the effect of adding phenolic resin on the final product; the left image is the product obtained after adding phenolic resin in Example 1; the right image is the product obtained in Comparative Example 3 without adding phenolic resin. DETAILED DESCRIPTION

[0022] The present invention can be better understood with reference to the following examples.

[0023] In the following examples, the chopped glass fibers have a length of 8 mm and a density of 0.16 g / cm 3 The length of the chopped ceramic fiber is 5 mm and the density is 0.12 g / cm 3 The binder is ethyl silicate Alumina 300nm, bulk density 4.1 g / cm 3 Carbon nanotubes have a diameter of 50nm and a length of 20µm Talc powder mesh number 3000, bulk density 2.8 g / cm 3 Hollow glass microspheres 40µm, bulk density 0.63 g / cm 3 The modified reinforced material needs to be cleaned with ethanol, immersed in an ethanol-water solution of a silane coupling agent for 6 hours, then filtered, and dried in an oven for 3 to 5 hours. Example 1

[0024] Resorcinol, formaldehyde, phenolic resin, ethanol, tetraethyl orthosilicate, and 3-(aminopropyl)triethoxysilane were added to a beaker in a molar ratio of 0.8:1.6:0.2:2.5:0.3:0.45, and stirred for 8 minutes to obtain solution A. The mass ratio of chopped glass fiber, chopped ceramic fiber, binder, and water was 0.5:0.5:2:25. First, add the binder to the water and stir until dissolved, add the fibers in batches and continue stirring for 20 minutes, then add 3% of the total mass ratio of modified reinforcing materials (alumina, carbon nanotubes, talcum powder, hollow glass microbeads in a molar ratio of 1:1:1:2), stir for 10 minutes, and obtain the reinforced composite fiber felt by wet filtration. The reinforced composite fiber felt was immersed in solution A and reacted at 30°C for 3 hours. The wet gel fiber composite material was then immersed in ethanol at 60°C for aging and washing, and the ethanol was changed every 12 hours for a total of 2 times, and then supercritically dried by CO2 for 4 hours to obtain a phenolic aerogel composite material. Ethanol and hexamethyldisilazane were stirred for 5 minutes at a molar ratio of 1:0.05 to obtain solution B. The obtained product was subjected to vacuum ion microwave treatment with solution B for 20 minutes to obtain a highly hydrophobic silicon-modified phenolic aerogel composite material. After characterization, it was found that the density of the composite aerogel material was 0.299g / cm 3 , with a specific surface area of ​​453m 2 / g, thermal conductivity at room temperature 0.0244 W / (m·k), hydrophobicity 99.1%, fire rating A2. Example 2

[0025] Catechol, acetaldehyde, phenolic resin, ethanol, tetraethyl orthosilicate, and 3-epoxypropyltriethoxysilane were added to a beaker in a molar ratio of 0.7:1.4:0.3:2.5:0.3:0.45, and stirred at room temperature for 10 minutes to obtain solution A. The mass ratio of chopped glass fiber, chopped ceramic fiber, binder, and water was 0.75:0.25:2:25. First, add the binder to the water and stir until dissolved, add the fibers in batches and continue stirring for 20 minutes, then add 3% of the total mass ratio of modified reinforcing materials (alumina, carbon nanotubes, talcum powder, hollow glass microbeads in a molar ratio of 1:1:1:2), stir for 10 minutes, and obtain the reinforced composite fiber felt by wet filtration. The reinforced composite fiber felt was immersed in solution A and reacted at 25°C for 3 hours. The wet gel fiber composite material was then immersed in acetone at 50°C for aging and washing, and the acetone was changed every 12 hours for a total of 2 times. It was then dried by microwave plasma for 20 minutes to obtain a phenolic aerogel composite material. Ethanol and dimethyldiethoxysilane were stirred for 8 minutes at a molar ratio of 1:0.15 to obtain solution B. The obtained product was subjected to vacuum ion microwave treatment with solution B for 25 minutes to obtain a highly hydrophobic silicon-modified phenolic aerogel composite material. After characterization, it was found that the density of the composite aerogel material was 0.316 g / cm 3 , with a specific surface area of ​​464m 2 / g, thermal conductivity at room temperature 0.0221 W / (m·k), hydrophobicity 99.5%, fire rating A2. Example 3

[0026] Hydroquinone, butyraldehyde, phenolic resin, ethanol, methyl orthosilicate, and 3-(aminopropyl)triethoxysilane were added to a beaker in a molar ratio of 0.9:1.8:0.1:2.5:0.3:0.45, and stirred at room temperature for 15 minutes to obtain solution A. The mass ratio of chopped glass fiber, chopped ceramic fiber, binder, and water was 0.75:0.25:2:25. First, add the binder to the water and stir until dissolved, add the fibers in batches and continue stirring for 20 minutes, then add 3% of the total mass ratio of modified reinforcing materials (alumina, carbon nanotubes, talcum powder, hollow glass microbeads in a molar ratio of 1:1:1:2), stir for 10 minutes, and obtain the reinforced composite fiber felt by wet filtration. The reinforced composite fiber felt was immersed in solution A and reacted at 50°C for 5 hours. The wet gel fiber composite material was then immersed in n-hexane at 70°C for aging and washing, and the n-hexane was changed every 12 hours for a total of 2 times. It was then dried at 50°C under normal pressure for 2 days to obtain a phenolic aerogel composite material. Ethanol and hexamethyldisilazane were stirred at a molar ratio of 1:0.2 for 4 minutes to obtain solution B. The obtained product was subjected to vacuum ion microwave treatment with solution B for 28 minutes to obtain a highly hydrophobic silicon-modified phenolic aerogel composite material with uniform color and regular shape (see Figure 1). After characterization, it was found that the density of the composite aerogel material was 0.332g / cm 3 , with a specific surface area of ​​302m 2 / g, thermal conductivity at room temperature 0.0306 W / (m·k), hydrophobicity 99.8%, fire rating A2. Comparative Example 1

[0027] Resorcinol, formaldehyde, phenolic resin, ethanol, tetraethyl orthosilicate, and 3-(aminopropyl)triethoxysilane were added to a beaker in a molar ratio of 0.8:1.6:0.2:2.5:0.3:0.45, and stirred for 5 minutes to obtain solution A. The mass ratio of chopped glass fiber, chopped ceramic fiber, binder, and water was 0.5:0.5:2:25. First, add the binder to the water and stir until dissolved, add the fibers in batches and continue stirring for 25 minutes, then add 3% of the total mass ratio of modified reinforcing materials (alumina, carbon nanotubes, talcum powder, hollow glass microbeads in a molar ratio of 1:1:1:2), stir for 10 minutes, and obtain the reinforced composite fiber felt by wet filtration. The reinforced composite fiber felt was immersed in solution A and reacted at 30°C for 4 hours. The wet gel fiber composite material was then immersed in ethanol at 60°C for aging and washing, and the ethanol was changed every 12 hours for a total of 2 times, and then supercritically dried by CO2 for 4 hours to obtain a phenolic aerogel composite material. Ethanol and hexamethyldisilazane were stirred for 5 minutes at a molar ratio of 1:0.05 to obtain solution B. The obtained product was subjected to vapor precipitation grafting with solution B for 8 hours to obtain a hydrophobic silicon-modified phenolic aerogel composite material. After characterization, it was found that the density of the composite aerogel material was 0.312g / cm3 , with a specific surface area of ​​402m 2 / g, thermal conductivity at room temperature 0.0257W / (m·k), hydrophobicity 87.2%, fire rating A2.

[0028] By comparing Example 1 with Comparative Example 1, it can be found that the vacuum ion microwave treatment shortens the hydrophobic modification time from the original 8 hours to 20 minutes, and the hydrophobicity of the composite material is also increased from the original 87.2% to 99.1%. This is because vacuum ion microwave treatment is a chemical bond grafting, while vapor deposition is mainly van der Waals force adsorption, and the former is more tightly and evenly bonded. Comparative Example 2

[0029] Resorcinol, formaldehyde, phenolic resin, ethanol, tetraethyl orthosilicate, and 3-(aminopropyl)triethoxysilane were added to a beaker in a molar ratio of 0.8:1.6:0.2:2.5:0.3:0.45, stirred for 7 minutes, and solution A was obtained. The mass ratio of chopped glass fiber, chopped ceramic fiber, binder, and water was 0.5:0.5:2:25. First, the binder was added to the water and stirred until dissolved, and the fibers were added in batches and stirred for 20 minutes, and the composite fiber felt was obtained by wet filtration. The composite fiber felt was immersed in solution A and reacted at 30°C for 3 hours. Then the wet gel fiber composite material was immersed in ethanol at 60°C for aging and washing, and the ethanol was changed every 12 hours, for a total of 2 times, and then supercritically dried by CO2 for 4 hours to obtain a phenolic aerogel composite material. Ethanol and hexamethyldisilazane were stirred for 5 minutes at a molar ratio of 1:0.05 to obtain solution B. The obtained product was subjected to vacuum ion microwave treatment with solution B for 17 minutes to obtain a highly hydrophobic silicon-modified phenolic-based aerogel composite material. Characterization revealed that the density of the composite aerogel material was 0.287 g / cm 3 , with a specific surface area of ​​438m 2 / g, thermal conductivity at room temperature 0.0297W / (m·k), hydrophobicity 99.1%, fire rating B1.

[0030] By comparing Example 1 with Comparative Example 2, it can be found that after adding the modified reinforcing material, the fire resistance level of the material is increased from the original B1 to A2, and the thermal conductivity at room temperature is reduced from 0.0297 W / (m·k) to 0.0244 W / (m·k). This is because the synergistic effect of various reinforcing materials causes the fire resistance and thermal conductivity to decrease. Comparative Example 3

[0031] Resorcinol, formaldehyde, ethanol, tetraethyl orthosilicate, and 3-(aminopropyl)triethoxysilane were added to a beaker in a molar ratio of 1:2:2.5:0.3:0.45, stirred for 5 minutes, and solution A was obtained. The mass ratio of chopped glass fiber, chopped ceramic fiber, binder, and water was 0.5:0.5:2:25. First, the binder was added to the water and stirred until dissolved, and the fibers were added in batches and stirred for 20 minutes. Then, a total mass ratio of 3% of the modified reinforcing material (alumina, carbon nanotubes, talcum powder, hollow glass microbeads in a molar ratio of 1:1:1:2) was added, stirred for 10 minutes, and the reinforced composite fiber felt was obtained by wet filtration. The reinforced composite fiber felt was immersed in solution A and reacted at 30°C for 3 hours. Then, the wet gel fiber composite material was immersed in ethanol at 60°C for aging and washing, and the ethanol was changed every 12 hours, for a total of 2 times, and then supercritical CO2 was dried for 4 hours to obtain a phenolic aerogel composite material. Ethanol and hexamethyldisilazane were stirred at a molar ratio of 1:0.05 for 5 minutes to obtain solution B. The obtained product was subjected to vacuum ion microwave treatment with solution B for 17 minutes to obtain a highly hydrophobic silicon-modified phenolic-based aerogel composite material. After characterization, it was found that the density of the composite aerogel material was 0.296 g / cm 3 , with a specific surface area of ​​466m 2 / g, thermal conductivity at room temperature 0.0242 W / (m·k), hydrophobicity 99.3%, fire rating A2.

[0032] By comparing Example 1 with Comparative Example 3, it can be found that after adding phenolic resin, the raw material cost is reduced by 20-30%, and in the SEM image (see Figure 2), the aerogel pore structure is more uniform and there is no agglomeration phenomenon. This is because in the process of growing the three-dimensional network structure, the phenolic resin directly serves as a growth site, accelerating the structure formation and thus avoiding agglomeration.

[0033] The present invention provides a low-cost hydrophobic phenolic-based aerogel fiber composite material and its preparation method and application ideas. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a low-cost hydrophobic phenolic-based aerogel fiber composite material, characterized in that: The steps include: (1) Solution A preparation: Phenol, aldehyde, phenolic resin, alcohol, silicate, and silane coupling agent are mixed evenly at a molar ratio of x:2x:1-x:2.5:0.3:0.45 to obtain solution A; wherein x<1; (2) Preparation of reinforced fiber felt: chopped glass fiber, chopped ceramic fiber, binder and water are mixed in a mass ratio of y:1-y:3:25 to obtain a mixed slurry, wherein y < 1; then 3-5% of the mass of the modified reinforcing material of the mixed slurry is added, the mixture is fully stirred and mixed, and then wet filtered to obtain a reinforced composite fiber felt; (3) impregnating the reinforced composite fiber felt obtained in step (2) into solution A in step (1), reacting at 20-50° C. for 3-5 hours to obtain a wet gel fiber composite material; (4) drying, aging, solvent replacement, and drying the wet gel fiber composite material obtained in step (3) to obtain a silicon-modified phenolic-based aerogel fiber composite material; (5) Solution B preparation: ethanol and silane hydrophobic agent are mixed at a molar ratio of 1:0.05-0.2 to obtain solution B; (6) The silicon-modified phenolic-based aerogel fiber composite material obtained in step (4) is subjected to vacuum ion microwave treatment using solution B to obtain.

2. The method for preparing a low-cost hydrophobic phenolic-based aerogel fiber composite material according to claim 1, characterized in that: In step (1), the silicate is methyl orthosilicate or ethyl orthosilicate; the phenol is any one of catechol, resorcinol or hydroquinone; the aldehyde is any one of formaldehyde, acetaldehyde and butyraldehyde; and the silane coupling agent is any one of 3-aminopropyltriethoxysilane and 3-epoxypropyltriethoxysilane.

3. The method for preparing a low-cost hydrophobic phenolic-based aerogel fiber composite material according to claim 1, characterized in that: In step (2), the chopped ceramic fibers have a length of 5-10 mm and a density of 0.16-0.18 g / cm 3 The chopped glass fibers have a length of 5 to 10 mm and a density of 0.09 to 0.12 g / cm 3 ; The binder is one of ethyl silicate and sodium silicate; the planes of the obtained reinforced composite fiber felt are partitioned.

4. The method for preparing a low-cost hydrophobic phenolic-based aerogel fiber composite material according to claim 1, characterized in that: In step (2), the modified reinforcing material is a mixture of alumina, carbon nanotubes, talcum powder, and hollow glass microspheres in a molar ratio of 0.5-1:0.5-1:0.5-1:1-3; the particle size of the alumina is 30nm~50µm, and the density is 3.9~4.2g / cm 3 The diameter of the carbon nanotubes is 30-80 nm, and the length is 10-30 µm; the mesh size of the talcum powder is 1000-3000, and the density is 2.7-2.8 g / cm 3 The hollow glass microspheres have a particle size of 10-60 µm and a bulk density of 0.49-0.68 g / cm 3 .

5. The method for preparing a low-cost hydrophobic phenolic-based aerogel fiber composite material according to claim 1, characterized in that: In step (2), firstly, a binder is added to water and stirred until dissolved, and then fibers are added in portions and stirred for 20 to 30 minutes, and then 3 to 5% of the total mass ratio of the modified reinforcing material is added; The modified reinforcement material needs to be washed with ethanol, immersed in an ethanol-water solution of a silane coupling agent for 5 to 7 hours, then filtered, and dried in an oven for 3 to 5 hours; The wet filtration adopts any one of low-pressure suction filtration, plate pressure filtration and mesh filtration.

6. The method for preparing a low-cost hydrophobic phenolic-based aerogel fiber composite material according to claim 1, characterized in that: In step (3), the reinforced composite fiber felt and the solution A are mixed in a volume ratio of 1:1-1.

5.

7. The method for preparing a low-cost hydrophobic phenolic-based aerogel fiber composite material according to claim 1, characterized in that: In step (4), the drying temperature is 50-80°C; the wet gel aging conditions are: aging at 50-80°C for 8-12 days, and the aging liquid is one of ethanol, acetone or n-hexane; the drying method is one of CO2 supercritical drying, microwave plasma drying or atmospheric pressure drying.

8. The method for preparing a low-cost hydrophobic phenolic-based aerogel fiber composite material according to claim 1, characterized in that: In step (5), the silane hydrophobic agent is hexamethyldisilazane and / or dimethyldiethoxysilane; In step (6), the vacuum ion microwave treatment method is as follows: in a closed container, solution B is placed at the bottom, the silicon-modified phenolic-based aerogel fiber composite material is suspended in the middle, the vacuum is evacuated to less than 100 Pa, and the temperature is heated to 35-50°C, and 2-3 GHz microwave radiation is used for 30s-1min, followed by standing for reaction for 4-10min, and then microwave radiation treatment is performed again, and repeated 2-3 times.

9. A low-cost hydrophobic phenolic-based aerogel fiber composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the low-cost hydrophobic phenolic-based aerogel fiber composite material according to claim 9 as a thermal insulation material in buildings and new energy vehicles.